Exploring the links between alexithymia and cognitive emotion regulation strategies in internet addiction: A network analysis model - Luo, Hongge; Gong, Xun; Chen, Xiaomei; Hu, Jianing; Wang, Xiaoyi; Sun, Yekun; Li, Jiating; Lv, Shaobo; Zhang, Xiujun (Frontiers in Psychology, 2022)
Alexithymia and emotion regulation are closely related to internet addiction. However, no research has examined how the different components of alexithymia are associated with cognitive emotion regulation in the context of multi-strategy use in internet addiction. The current study aimed to investigate the relation between alexithymia and cognitive emotion regulation in individuals with internet addiction via network analysis. Participants included 560 students with Young’s Internet Addiction Test scores greater than 50 points; they were also asked to complete the Toronto Alexithymia Scale (TAS-20) and the Cognitive Emotion Regulation Questionnaire (CERQ). The results revealed two bridge nodes emerging within the combined alexithymia and cognitive emotion regulation network model: “catastrophizing” and “externally oriented thoughts.” These findings indicate a more specific relation between alexithymia and cognitive emotion regulation and provide empirical evidence for targeted prevention and targeted interventions for internet addiction.